Radiation Dose Obtained from Whole Body Bone Scans - Patsuree Cheebsumon, Ph.D (Journal of The Department of Medical Services, 2021)
Background : Radiation dose obtained from bone scan examination in nuclear medicine is able to know for reducing radiation anxiety. Objective : The aim of this study was to measure the radiation exposure from bone scan examinations in different time after injection and distance. Method : Twenty-four bone scans at 2-inches under umbilicus were measured at 0.25, 0.5, 1, and 1.5 metres, and also time after immediately injection, 30, 60, 90, 120 and 222 minutes, respectively. Results : Radiation exposure significantly reduced when time after injection and distance were increased (p<0.05). In this condition, maximum radiation dose of person who worked outside nuclear medicine was 300 μSv for 180 minutes at a distance of 0.25 metre. Conclusion : Radiation dose obtained from bone scan examinations decreased when distance and time after injection increased. In case of additional diagnostic tools, one hour after injection was recommended. To ensure radiation safety should spend time less at optimal distance.